Altmetrics for research outputs measurement and scholarly information management - Erdt, Mojisola (Springer Nature Singapore Pte Ltd., 2018)
This book constitutes the refereed proceedings of the International Workshop on Altmetrics for Research Outputs Measurements and Scholarly Information Management, AROSIM 2018, held in Singapore, in January 2018. The 7 revised full papers presented together with two keynote papers and one introduction paper were carefully reviewed and selected from 20 submissions. The workshop will investigate how social media based metrics along with traditional and non-traditional metrics can advance the state-of-the-art in measuring research outputs.